PENGARUH LAYANAN BIMBINGAN SOSIAL DAN LAYANAN BIMBINGAN KELOMPOK TERHADAP PERILAKU BULLYING - Werdamukti, F Intan; Widodo, Bernardus (Educatio Vitae, 2017)
Bullying is an act that a person deliberately makes another person feel afraid or terancam.Pada this study, researchers will examine two factors: social counseling services and group counseling services. This study aims to investigate the influence of social counseling services and group counseling services to bullying behavior. The population in this study were all students of class XI Year 2016-2017 which behaves bullying based on data from the counselor in April-June of 60 students spread into 10 classes. Mechanical sampling using sampling techniques saturated, ie sampling technique when all members of the population used as a sample. Thus the total sample of 60 students Data obtained using the questionnaire method shaped the scale of the scale of bullying behavior, social counseling services scale, and the scale of group counseling services. In this study, the authors propose three hypotheses are: a hypothesis first minor (XI) reads guidance services social influence significantly against bullying, minor hypothesis second (X2) reads guidance services group gave a significant influence on the behavior of bullying, major hypothesis (Y) social counseling services and guidance services group gave a significant influence on the behavior of bullying. Data were analyzed using Chi Square test. The research found that the hypothesis of counseling services social influence significantly against bullying behavior is rejected, because the chi squared count <chi kuadart table 5% (0.601 <3.841), the hypothesis of guidance the group gave a significant influence on the behavior of bullying is accepted, Because chi squared count> chi kuadart table 5% (9.568> 3.841). , So the hypothesis of social counseling services and group counseling services provide significant influence on bullying behavior is rejected, because the chi squared count <chi kuadart table 5% (0.601 <3.841) .Kesimpulannya based on the results of the analysis that the first minor hypothesis (X1) is rejected, the hypothesis the second (X2) and major hypothesis is accepted (Y) was rejected.